FAO/IPGRI Technical guidelines for the safe movement of small fruit germplasm - Diekmann, M.; Frison, Emile A.; Putter, T.; Food and Agriculture Organization of the United Nations; International Plant Genetic Resources Institute (1994)
Published in collaboration with the Small Fruit Virus Working Group of the International Society for Horticultural Sciences